Tracking the spatial patterns and thematic dynamics of GRACE satellite application over the last 20 years (2002–2022) - Zhang, Hongyue (Frontiers in Earth Science, 2024)
The GRACE (Gravity Recovery and Climate Experiment) satellite, operational from its launch in 2002 until October 2017, documented critical changes in global terrestrial water storage, significantly advancing the fields of gravity field analysis, hydrological variations, and environmental monitoring. This study investigates the thematic evolution of 2,966 SCIE-indexed publications on GRACE satellite applications from 2002 to 2022, utilizing co-occurrence network mapping and complex network analysis. Our results indicate a steady growth in GRACE satellite application research, with early publications (2002–2004) achieving an average citation rate exceeding 100, underscoring their substantial impact. Keyword clustering identified four primary research themes: Hydrology and Water Resources, Atmospheric and Environmental Science, Geophysical and Temporal Analysis, and Polar and Glaciological Studies. Over time, these themes have expanded and deepened, transitioning from initial focuses on gravity field computations to hydrological applications, sea level studies, and more specific investigations into water resources, climate change, and advancements in satellite geodesy. Recent research has particularly concentrated on groundwater and water storage issues. Geographically, the United States leads in publication output, impact, and international collaborations, with China following in publication count and network centrality, albeit with potential for improved impact. European countries demonstrate significant influence and centrality within the cooperation network. The evolution index of the international cooperation network shows a significant increase in connectivity from 2002 to 2022, with closer cooperation between countries. There is notable growth in both the number and intensity of collaborations, as evidenced by the rising average degree and average weighted degree. Overall, these indices underscore the evolution towards a more connected and globally integrated research network in GRACE satellite research. Looking forward, technological advancements, enhanced international collaboration, and integration with other data sources will drive future research in GRACE satellite application research, with important implications for addressing global environmental and climate challenges.